Value Co-creation in Service Innovation: Makermet Case Study - Safade, Lana (2015)
The dissertation attempts to explore how professional service providers engage in value co-creation with clients, taking into account the engagement platforms in co-creation. Managing value co-creation in services is a critical matter for the innovation of the company especially in B2B service context where high interactivity exists. Understanding how engagement platforms provide opportunities for co-creation is a building block in understanding how then value is leveraged. Being able to map out the value co-created sets guidelines of how each party; whether it was the firm or the client use the co-created value in new services development. A qualitative research method is employed through investigating " Makermet ", which is a branding and marketing consultancy firm. Engagement platforms with clients are studied through observations, and the leverage of value is studied through both observations and semi-structured interviews. The dissertation builds on theory from professional services marketing, engagement platforms, and co-creation in service innovation. The findings of the research conclude that in a complex professional service firm, the co-created value is embedded in the business operations which makes it a challenge to innovate new services through co-creation and rather learn with customers to innovate. Therefore, in order to achieve the level of service innovation through co-creation new engagement platforms should be presented and service innovation should be treated as a process that is integrated within the other company processes.